The effect of gluon condensate on the DC conductivity and butterfly effect - Jing Zhou; Saiwen Zhang (Physics Letters B)
In this work, we study the effect of gluon condensate on the DC conductivity and butterfly effect using AdS/CFT. First, by considering the butterfly velocity defined by the metric, we find that the butterfly velocity decreases with the increase of gluon condensate parameter c. This indicates that gluon condensation increases the disorder or chaotic behavior within the system. Next, we expand the drag force into an expression for the butterfly velocity and find that the presence of butterfly velocity increase the magnitude of the drag force. Finally, we investigate the relationship between butterfly velocity and DC conductivity, and find that DC conductivity rises as the butterfly velocity increases. This behavior may be interpreted as a manifestation of enhanced order in the system.